A Conceptual Review of Jalauka and Jalaukaavcharana (Leech-Therapy) in Ayurveda - Jasrotia, Mridu; Shinde, Sandeep; Gandhi, Sachin (International Research Journal of Ayurveda & Yoga, 2022)
Jalaukaavcharana (Leech therapy) is one of the form of Raktmokshana. Jalauka (Leeches) are used for impure blood letting The two types of treatment that are advised in Ayurveda are:-1). Shaman chikitsa and 2). Shodhana chikitsa. Shamana chikitsa means Internal medicine and Shodhana chikitsa means Elimination therapy. In Ayurveda, Panchkarma is one of the tools to treat many disorders. Acharya Sushruta included Raktmokshana in Panchakarma. The first description about the Jalauka (Leech) is mentioned in Sushruta Samita.The term"Jalauka"(Leech) means, a creature whose life depends on water. Jalauka is having various names which are - Jalita, Jalauka , Jalatani. Jalauka is the only Shodhana treatment that can be done on Children ,Ladies , weak , old , rich and fearful person . It is mainly indicated for Vitiated Pittaja and Raktaja doshas. Modern Scientists and Physicians also describe Leech and Leech saliva having Anti -Septic, Anti-Biotic and Anti-Coagulant properties.